Association between poor sleep quality and an increased risk of dry eye disease in patients with obstructive sleep apnea syndrome - Pu, Qi; Wu, Zhen; Li, Ao-Ling; Guo, Xiao-Xiao; Hu, Jing-Jie; Li, Xin-Yu (Frontiers in Medicine, 2022)
Purpose: Obstructive sleep apnea (OSA) is related to an increased incidence of dry eye disease (DED). However, their exact relationship is unknown and requires further well-designed studies with advanced mechanisms detection. Patients and Methods: This case-control study included 125 OSA cases and 125 age-gender matched controls enrolled in the hospital between Jan 1st and Oct 1st, 2021. OSA diagnosis and classification were performed using a Polysomnography (PSG) assay. Detailed ophthalmological examinations, including the Schirmer I test, corneal staining, and ocular surface disease index (OSDI), were used to detect DED-related parameters. A comprehensive ocular surface assay was performed to measure a series of parameters, including first non-invasive first tear film break-up time (f-NIBUT), average non-invasive first tear film break-up time (av-NIBUT), tear meniscus height (TMH), and loss of meibomian gland. Additionally, the Pittsburgh Sleep Quality Index (PSQI) scale was used to assess sleep quality. Results: Compared to the control, the OSA group showed an increased DED risk (P=0.016) along with an increased PSQI score and a higher rate of poor quality sleep (P<0.001 and P=0.007, respectively). Stratification of OSA cases indicated that DED-related parameters were impaired in patients with severe OSA (P<0.05). The analysis of DED-parameters-related factors showed significant correlations between OSA-related indexes and PSQI (P<0.05). Moreover, the poor sleep quality group in the OSA cases showed worse DED-related parameters (P<0.05), which was not observed in the control group. Conclusions: OSA, especially the severe stage OSA, was related to an increased risk of DED. Also, sleep quality was correlated to the onset of both OSA and DED, where poor sleep quality revealed a relationship between OSA and the risk of DED. Overall, our findings provided evidence for advanced management of DED and OSA in the future.